Analisis Perbandingan Hasil Spektrum Magnetic Resonance Spectroscopy Brain Dengan Variasi Ukuran Volume of Interest (VOI) Pada MRI Phillips 3T - Aunisa Icha; Legia Prananto; Guntur Winarno (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: Technically, by applying MR Spectroscopy it possibly makes that signal from several numbers of different chemical compounds can be obtained, separated, and quantified in simultaneous way. In relation to which, the quantification of brain metabolites in 1H MRS depends on the separation of spectroscopy signal of each metabolites. In this matter, spectrum results will be influenced by the size of volume of interest. In this matter, volume of interest (VOI) is a specific area in the tissue, whereby the metabolites of which, are analyzed. This research aims to analyze the comparison of the results of brain MRS spectrum with the different variation of Volume of Interest (VOI) measurements in MRI Phillips 3T.Methods: Design of this research applies quantitative method with experimental approach by using Philips Ingenia 3 Tesla MRI machine undertaken at radiology installation of Regional General Hospital Ciawi toward 11 brain MRI patients undergoing Magnetic Resonance Spectroscopy with the different variation size of Volume of Interest (VOI) namely 1.0 × 1.0 ×1.0 cm, 1.5 × 3.0 ×1.5 cm, and 2.0 × 2.0 × 2.0 cm.Results: This research suggests that there is a different height of NAA, Choline, Creatine, and Glx metabolites whereas for Myo-inositol, Lipids and Lactate metabolites there is not any significant difference. Meanwhile for Full Width Half Maximum, there is a significant difference with different variation of volume of interest (VOI).Conclusions: There is a significant difference in the height of metabolites NAA, Choline, Creatine, Glx (p value 0,05), whereas for metabolites of Myo-Inositol, lipids, and Lactate (p value 0,05) there were no significant differences at different variations of Volume of Interest (VOI). There is a significant difference with a p value of 0.000 0.05 in the Full Width Half Maximum (FWHM) value with different Volume of Interest (VOI) variations where the highest average Full Width Half Maximum (FWHM) value is VOI C (2.0 × 2.0 × 2, 0 cm) with an average of 21.476 followed by VOI B (1.5 × 3.0 × 1.5 cm) of 20.603 and the lowest average FWHM value is VOI A (1.0 × 1.0 × 1.0 cm) of 15.985 which means that the larger the size of the Volume of Interest (VOI), the higher the Full Width Half Maximum (FWHM) value will be. The size of the Volume of Interest (VOI) for the hippocampus area must be adjusted to the size of the patient's hippocampus because a size that is too large will cause unwanted areas to enter the Volume of Interest (VOI) and affect the spectrum results.